Zinc supplementation prior to heat shock enhances HSP70 synthesis through HSF1 phosphorylation at serine 326 in human peripheral mononuclear cells. Issue 17 (12th August 2022) - Peng-Winkler, Yifan; Büttgenbach, Anna; Rink, Lothar; Wessels, Inga
Abstract : Acute alteration of the functional zinc status increases the HSP70 protein level after heat shock in peripheral blood mononuclear cells (PBMC), while zinc deficiency, but not zinc supplementation, further augments heat shock-induced cell death. Abstract : Zinc supplementation prior to heat shock increases HSP70 (heat shock protein 70) expression, which has cytoprotective effects in tissue cells during inflammation. Effects of zinc deficiency in this regard have been discussed controversially. Whether zinc modulates the expression of HSP70 in the human immune system as well and thus affects cell survival during heat stress is so far largely unknown. Therefore, we investigated the effect of alterations in the cellular zinc status on HSP70 expression and on cellular survival in human monocytes and lymphocytes. Three cell lines (Jurkat, THP-1, and Ramos) and enriched primary human monocytes and lymphocytes from young subjects were subjected to zinc deficiency or supplementation and subsequently heat shock at 42 °C. HSP70 mRNA expression was analyzed by real-time PCR, whereas HSP70 protein expression was analyzed by western blotting. In all cells other than Ramos cells, zinc supplementation and deficiency augmented heat shock-induced HSP70 expression. Further experiments in primary monocytes and lymphocytes indicated that this may be explained by the enhanced phosphorylation of HSF1 (Heat shock factor 1) at Ser326, which plays a significant role in HSP70 induction, as observed in zinc deficient and supplemented cells. While zinc supplementation had negligible effects on cell viability, acute zinc deficiency further increased cell death, induced by heat shock. Our results emphasize the importance of an optimal cellular zinc status. Moreover, we present a possible mechanism behind zinc's influence on HSP70 expression in human leukocytes. Our data form the basis for further in vivo and ex vivo studies to investigate how the zinc status may affect cellular damage in transient high temperature situations.